Multicentre observational study of the Gatekeeper™ for faecal incontinence. Issue 3 (1st December 2015) - Ratto, C.; Buntzen, S.; Aigner, F.; Altomare, D. F.; Heydari, A.; Donisi, L.; Lundby, L.; Parello, A.
Abstract : Background: A variety of therapeutic approaches are available for faecal incontinence. Implantation of Gatekeeper™ prostheses is a new promising option. The primary endpoint of this prospective observational multicentre study was to assess the clinical efficacy of Gatekeeper™ implantation in patients with faecal incontinence. Secondary endpoints included the assessment of patients' quality of life, and the feasibility and safety of implantation. Methods: Patients with faecal incontinence, with either intact sphincters or internal anal sphincter lesions extending for less than 60° of the anal circumference, were selected. Intersphincteric implantation of six prostheses was performed. At baseline, and 1, 3 and 12 months after implantation, the number of faecal incontinence episodes, Cleveland Clinic Faecal Incontinence, Vaizey and American Medical Systems, Faecal Incontinence Quality of Life Scale and Short Form 36 Health Survey scores were recorded. Endoanal ultrasonography was performed at baseline and follow‐up. Results: Fifty‐four patients were implanted. After Gatekeeper™ implantation, incontinence to gas, liquid and solid stool improved significantly, soiling was reduced, and ability to defer defaecation enhanced. All faecal incontinence severity scores were significantly reduced, and patients' quality of life improved. At 12 months, 30 patients (56 per cent) showed at least 75 per cent improvement in all faecal incontinence parameters, and seven (13 per cent) became fully continent. In three patients a single prosthesis was extruded during surgery, but was replaced immediately. After implantation, prosthesis dislodgement occurred in three patients; no replacement was required. Conclusion: Anal implantation of the Gatekeeper™ in patients with faecal incontinence was effective and safe. Clinical benefits were sustained at 1‐year follow‐up. Abstract : Gatekeeper TM effective